2018
DOI: 10.1039/c8fo01329b
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of in vitro digestion on the functional properties of Psidium cattleianum Sabine (araçá), Butia odorata (Barb. Rodr.) Noblick (butiá) and Eugenia uniflora L. (pitanga) fruit extracts

Abstract: This study evaluated the effect of in vitro digestion on the functional properties of three Brazilian native fruit extracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…As a reason of this decrease, it can be hypothesized that biological reactivity of antioxidant compounds can alter during in vitro digestion and they may less reactive at pH ~7.4 in intestinal digestion. Moreover, similar results were reported for some fruits and vegetables in the other studies, as well (Vinholes et al, 2018;Goulas and Hadjisolomou, 2019;Tomas et al, 2021). The decrease in TAC was observed with both methods after in vitro gastro-intestinal digestion, may be related to the reduction in bioactive antioxidant compounds such as total phenolics and total anthocyanins (de la Fuente et al (2019).…”
Section: Changes In Tac Of the Extracts During In Vitro Digestionsupporting
confidence: 85%
“…As a reason of this decrease, it can be hypothesized that biological reactivity of antioxidant compounds can alter during in vitro digestion and they may less reactive at pH ~7.4 in intestinal digestion. Moreover, similar results were reported for some fruits and vegetables in the other studies, as well (Vinholes et al, 2018;Goulas and Hadjisolomou, 2019;Tomas et al, 2021). The decrease in TAC was observed with both methods after in vitro gastro-intestinal digestion, may be related to the reduction in bioactive antioxidant compounds such as total phenolics and total anthocyanins (de la Fuente et al (2019).…”
Section: Changes In Tac Of the Extracts During In Vitro Digestionsupporting
confidence: 85%
“…These results are confirmed in other studies in the literature conducted on plant matrices (bamboo leaves, Butia, and Carob fruits). At the end of the oral phase, there is an initial and partial degradation of the phenolic compounds [52][53][54]. Furthermore, as reported by Leonard et al (2020) [25], there is a strong interaction between fibre and phenols.…”
Section: Total Phenolic Content Of In Vitro Digested Samplesmentioning
confidence: 72%
“…ese results indicated that the sample had a stronger effect on the DPPH-radical scavenging ability at the oral and gastric digestion stages but a weaker effect at the intestinal digestion stage. e rapid loss of antioxidant activity after the intestinal digestion stage occurs in other foods, such as bamboo leaf soup [20], persimmon fruit [13], pomegranate peel [36], and some Brazilian fruits [37].…”
Section: Effect Of In Vitro Digestion On the Antioxidant Activity Of ...mentioning
confidence: 99%